The pre-technical project, a demonstration in education for technology. medical technology, 11th and 12th year - New York City Board Of Education, Brooklyn, NY.; New York City Board of Education, Brooklyn, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1967)
Medical technology is one of three offerings of the pretechnical project designed to remotivate underachieving high school students who, upon successful completion of the program, may be admitted to the career programs of the community college. Developed by a committee of teachers at the local level, the manual is intended to assist teachers, supervisors, and administrators in operating the project. Students, selected for the program at the end of the 10th year, are blocked-programed for English, science, mathematics, and a technical laboratory for 16.5 hours per week, but mix with other students for the remaining classes. Team teaching, interdisciplinary correlation, and a laboratory-type curriculum are used. Program aims, student selection, organization and administration, student evaluation, recordkeeping, guidance procedures, and teacher role are discussed in detail. Outlines of correlated units in English, mathematics, and science constitute the major portion of the manual. Examples of science units, the focus of the correlation, for the year are (1) energy and the structure of matter, (2) the chemical equation and mathematical applications, and (3) nuclear chemistry. Examples of twelfth year units are (1) physical and chemical properties of protoplasm, (2) the chemistry of energy supplies, (3) the origin of life and levels of organization, (4) infections and functional disorders, and (5) the science of immunology and modern chemotherapy. For other project offerings, see vt 005 279--vt 005 281. Single copies of this document are available to school systems without charge from correlated and pre-technical programs, 480 pacific street, brooklyn, New York 11217. (jk)
Educational level discussed: Grade 11.
Educational level discussed: Grade 12.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Allied Health Occupations Education; Curriculum Guides; Experimental Curriculum; Grade 11.; Grade 12.; Pretechnology Programs; Program Guides; Teaching Guides; Teaching Methods; Underachievement